Conflict management and dispute settlement in East Asia - Amer, Ramses; Zou, Keyuan (Ashgate Pub., 2011)
Conflict and disputes exist everywhere in human society, at the international, regional, and national levels. The management and settlement of them has become an imperative. This title studies the management settlement of conflict and disputes in East Asia.